Kuzguncuk as a village of mutual respect and harmony: myth or reality? - (:unkn) unknown (My University, 2011)
My research concentrates on the Jews of Istanbul and especially on the Kuzguncuk neighbourhood. My aim is to understand the changes within the social structure of the Jewish community of Turkey and its relationship with the dominant Muslim society. Different from other important Jewish neighbourhoods of Istanbul such as quarters in Balat, Haskoy and Galata-Pera district, Kuzguncuk is known as the "village of harmony" and a "place in which all religious and ethnic groups live in peace, harmony and mutual respect". In this article, I try to answer the question of whether this is a myth or the real experience of Kuzguncuk. Whether a myth or a real experience, can it be a model for people "living together in peace and harmony"? I will also explore the situation of Jews after the foundation of the Turkish republic. In order to understand the changing structure of Jews of Kuzguncuk, I conducted interviews with seven actual and former residents of Kuzguncuk, who now live in Israel, Kuzguncuk and other districts of Istanbul. © 2011 Copyright Taylor and Francis Group, LLC.